Optimalisasi Produksi dan Bauran Pemasaran dalam Mendorong Kinerja Peternakan Ayam Petelur Bumdes Bungung Rumbiaya Desa Tanakaraeng - Andi Arifuddin Iskandar; Agussalim Patola DM; Nur Qalbi Tayibu (Politeknik Piksi Ganesha Indonesia, 2026)
The Bungung Rumbiaya Village-Owned Enterprise (BUMDes) faces the challenge of declining productivity in its egg-laying chicken business due to poor drinking water quality and conventional marketing strategies. This Community Service Program aims to address these dual challenges through a Participatory Action Research (PAR) approach, which emphasizes collaboration and empowerment of partners as active subjects. The implementation method consists of three participatory PAR cycles: (1) joint planning to identify problems and solutions, (2) collective action in technology implementation, and (3) reflection for evaluation and further planning. The program's results demonstrated two key achievements. First, the implementation of a water filtration system (1,000-liter tank, water tower, and multi-layer filter) successfully improved water quality, directly impacting egg production by 10-15% and improving chicken health. Second, the development of the Village-Owned Enterprise (BUMDes) website (https://bungungrumbiaya.com) successfully laid the foundation for digitalized marketing. More important than these technical outputs, there was a significant increase in partner capacity and independence, with administrators now able to operate and maintain the technology independently. The program concluded that integrating appropriate technology and the PAR approach is an effective strategy for creating sustainable solutions and empowering village institutions. Maintaining sustainability requires a commitment to regular maintenance from partners, as well as continued mentoring from universities and the village government.